Toll-like receptors and their role in the pathogenesis of myasthenia gravis: a comprehensive review - Zheng, Xiaoxiao; Li, Ling; Ma, Hongyue; Zhu, Mingxia; Li, Xiuli; Feng, Xinhong (Frontiers in Immunology, 2025)
Myasthenia gravis (MG) is a chronic autoimmune neuromuscular disorder marked by autoantibody-mediated dysfunction at the neuromuscular junction, resulting in fluctuating muscle weakness. The pathogenesis of MG involves a complex interplay between genetic predisposition, environmental factors, and immune system dysregulation. Among these, the innate immune system, particularly Toll-like receptors (TLRs), has emerged as a critical player in disease progression by influencing both innate and adaptive immunity. TLRs are a family of pattern recognition receptors (PRRs) that detect pathogen-associated molecular patterns (PAMPs) and damage-associated molecular patterns (DAMPs), triggering immune responses. Dysregulation of TLRs expression and signaling in MG has been implicated in chronic inflammation, breakdown of immune tolerance, and activation of autoreactive T and B cells. Overexpression of specific TLRs, such as TLR4 and TLR9, has been reported in MG patients, particularly in thymic tissues and peripheral immune cells, correlating with increased pro-inflammatory cytokine production and autoantibody generation. These aberrant responses contribute to the autoimmune cascade that underlies MG. Emerging evidence highlights the therapeutic potential of targeting TLRs pathways in MG. Strategies include using TLRs antagonists, modulating downstream signaling pathways, and leveraging epigenetic regulators to normalize TLRs activity. This review examines the role of TLRs in MG by exploring their expression profiles, their involvement in inflammatory signaling pathways, their impact on the adaptive immune system, and their potential as therapeutic targets. A better understanding of the role of TLRs in MG pathogenesis could open new avenues for modulating immune responses and precision therapies targeting the innate immune system.